Inside Room 111: Being a Responsive Educator through Fostering an Adolescent-Centered Community of Care in the COVID-19 Pandemic - Cheryl R. Ellerbrock; Ashlee Highfill (Middle Grades Review, 2022)
The 2021-2022 school year came with the mantra of “learning loss” and the push to fill in the learning gaps and “accelerate learning” at all costs. In an effort to return education to “normal” and reduce learning loss, what transpired for many was a lack of focus on the students’ pandemic experiences and its effect on their lives from a wholistic perspective. Education is at a point where “normal” needs to be re-defined to support students’ needs and their learning, requiring middle level teachers to be responsive educators. Middle level educators can be responsive to their students’ needs is by fostering an adolescent-centered community of care. Elements of an adolescent-centered community of care include responsive organizational structures, responsive teacher characteristics and practices grounded in care and advocacy, and positive and supportive peer relationships. This article highlights how one middle level teacher enacted a community of care for her young adolescents to best reach and teach them upon the return to in-person teaching in the COVID-19 pandemic.
Keywords: Adolescent-centered Community of Care; Developmental Responsiveness; Cultural Responsiveness; Teacher Care; Teacher Characteristics; Teacher Practices; Organizational Structures; Peer Relationships; Advocacy